Nestin and vimentin colocalization affects the subcellular location of glucocorticoid receptor in cutaneous melanoma. Issue 3 (16th October 2012) - Lai, Simone; Piras, Franca; Spiga, Saturnino; Perra, Maria Teresa; Minerba, Luigi; Piga, Michela; Mura, Ester; Murtas, Daniela; Demurtas, Paolo; Corrias, Michela; Maxia, Cristina; Ferreli, Caterina; et al.
<x xml:space="preserve">Abstract</x> Aims: Nestin (a neuronal stem cell/progenitor cell marker of central nervous system development), vimentin (which is ubiquitously expressed in mesenchymal cells), and the glucocorticoid receptor (GR, which is involved in the immune response, cell proliferation, and apoptosis) have been shown to interact in embryonic and undifferentiated tissues in modulating cell proliferation. The aim of this study was to analyse nestin, vimentin and GR expression in tumour tissue (melanoma), and their association with clinicopathological variables, to evaluate any effect on tumour progression. Methods and results: Immunohistochemistry, double‐label immunofluorescence and confocal laser scanning microscopy were performed on biopsy specimens of cutaneous melanoma from 81 patients. Fisher's and Pearson's tests showed a correlation between nestin, vimentin and subcellular GR location (P = 0.008). Their concomitant expression also correlated with Clark level and thickness (P = 0.02 and P = 0.029, respectively). Kaplan–Meier analysis revealed a poorer outcome for stage III and IV patients with associated expression of nestin, vimentin and cytoplasmic GR in tumour tissue (P = 0.02). Conclusions: These results suggest the presence in melanoma of growth mechanisms involving nestin, vimentin, and GR, similarly to that occurring in embryonic and undifferentiated cells, and may help in understanding tumour biology to provide a molecular basis for clinical therapies.